Trends in metajournalistic discourse analysis in Brazilian political coverage by U.S. newspapers (Intercom - Brazilian Journal of Communication Sciences, 2026)
This article presents trends in the analysis of metajournalistic discourse in Brazilian political coverage by U.S. newspapers. Metajournalistic discourse is defined as professionals engaging in discussions, both within and outside the profession, about its normative foundations. The hypothesis is that US news outlets have historically used approaches that are less anchored in the value of detachment when covering issues related to other countries. Prominent trends in contemporary studies on metajournalistic discourse include the journalistic approach to populist political leaders from the far-right political spectrum around the world and the treatment of issues that challenge the constitutional principles of the United States, even though such legal principles differ in other countries.
Keywords: Journalism; Metadiscourse; Brazil; United States.